2019
DOI: 10.1002/jgh3.12267
|View full text |Cite
|
Sign up to set email alerts
|

Is water‐soluble contrast enema examination for integrity of rectal anastomosis necessary prior to ileostomy reversal?

Abstract: Background and Aim Routine use of water‐soluble contrast enema (WSCE) to assess anastomotic integrity is debated. This study aimed to evaluate the role of WSCE to assess anastomotic integrity following anterior resections (AR) with defunctioning stoma prior to reversal and identify factors to limit its selective use. Methods This retrospective study evaluated all WSCE performed over a 7‐year period at a high‐volume colorectal unit. Risk factors for radiological abnormality/leak, including malignancy, chemoradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…However, most centres will perform pre‐reversal investigations, with a preference of a contrast enema 3–7 . Our study has shown the importance of performing both WSCE and FS.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…However, most centres will perform pre‐reversal investigations, with a preference of a contrast enema 3–7 . Our study has shown the importance of performing both WSCE and FS.…”
Section: Discussionmentioning
confidence: 87%
“…The routine use of investigations prior to ileostomy reversal has been questioned and the accuracy of these tests can be variable 3–7 . For example, a ‘dog ear’ at the stapled anastomosis may be misinterpreted as a leak, or a stricture being incorrectly described due to a lack of anastomotic distension on WSCE 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A leak is diagnosed by the examining radiologist identifying extraluminal iodinated contrast first introduced through the anus via a catheter. WSCE utilizes x-ray fluoroscopy to investigate the flow of contrast through the anastomosis with representative fluoroscopic images acquired, supplemented by higher quality radiographs when required [11]. WSCE using x-ray fluoroscopy has a number of limitations, including limited accuracy with a sensitivity of 78% and a positive predictive value of 62% [10], use of ionizing radiation (particularly relevant for younger patients), limited two-dimensional images, paucity of anatomical information and diminishing fluoroscopy capacity in the UK National Health Service (NHS) and North America, with associated decrease in fluoroscopic skills and interpretative expertise [12].…”
Section: Introductionmentioning
confidence: 99%
“…WSCE using x-ray fluoroscopy has a number of limitations, including limited accuracy with a sensitivity of 78% and a positive predictive value of 62% [10], use of ionizing radiation (particularly relevant for younger patients), limited two-dimensional images, paucity of anatomical information and diminishing fluoroscopy capacity in the UK National Health Service (NHS) and North America, with associated decrease in fluoroscopic skills and interpretative expertise [12]. Unsurprisingly, therefore, some surgeons consider clinical assessment superior and sufficient, questioning the need for routine WSCE [10,11,13]. Where WSCE has been requested, presacral widening is a relatively frequent finding, with MRI or CT required to interrogate the cause.…”
Section: Introductionmentioning
confidence: 99%